Wisdom from the Monastery: The Rule of St. Benedict for Everyday Life - Coff, Pascaline (Cistercian studies quarterly, 2006)
The article reviews the book "Wisdom from the Monastery: The Rule of St. Benedict for Everyday Life," translated by Patrick Barry.